2015
DOI: 10.1016/j.jnucmat.2014.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Displacement cascades and defects annealing in tungsten, Part I: Defect database from molecular dynamics simulations

Abstract: Molecular dynamics simulations have been used to generate a comprehensive database of surviving defects due to displacement cascades in bulk tungsten. Twenty one data points of primary knock-on atom (PKA) energies ranging from 100 eV (sub-threshold energy) to 100 keV (∼780×E d , where E d is the average displacement threshold energy) have been completed at 300 K, 1025 K and 2050 K. Within this range of PKA energies, two regimes of power-law energy-dependence of the defect production are observed. A distinct po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
88
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 22 publications
10
88
0
1
Order By: Relevance
“…The cascade is initiated by giving a random primary-knock-on-atom (PKA) near the center of the cell an initial velocity with a random direction. In keeping with our comparison to previous work [10][11][12][13], the simulations did not treat electronic stopping. To first order, neglecting electronic losses amounts to an energy shift which is related to the difference between the true PKA energy and the MD cascade energy; the latter of which is essentially equivalent to the damage energy in the Norgett-Robinson-Torrens (NRT) displacement model [11,14].…”
Section: Methodsmentioning
confidence: 87%
“…The cascade is initiated by giving a random primary-knock-on-atom (PKA) near the center of the cell an initial velocity with a random direction. In keeping with our comparison to previous work [10][11][12][13], the simulations did not treat electronic stopping. To first order, neglecting electronic losses amounts to an energy shift which is related to the difference between the true PKA energy and the MD cascade energy; the latter of which is essentially equivalent to the damage energy in the Norgett-Robinson-Torrens (NRT) displacement model [11,14].…”
Section: Methodsmentioning
confidence: 87%
“…Although the MD results show a higher FP production than in Ref. [142] and a lower FP production than in…”
Section: Damage Cascades Validation Calculated With the Srim Code 34mentioning
confidence: 50%
“…As can be seen in Figure 3.10, the results are similar to those previously published in the literature. Setyawan et al [142] , Troev et al [143] and Caturla et al [144]. Comparing MD results at 300 and 1000 K, it can be observed that the higher the temperature, the higher the recombination rate.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations